Comparative Efficacy of Continuous Ceftazidime Infusion vs. Intermittent Bolus against In Vitro Ceftazidime-Susceptible and -Resistant Pseudomonas aeruginosa Biofilm - Cristina El Haj; Eugènia Agustí; Eva Benavent; Laura Soldevila-Boixader; Raül Rigo-Bonnin; Fe Tubau; Benjamín Torrejón; Jaime Esteban; Oscar Murillo (MDPI AG, 2024)
Background: As the anti-biofilm pharmacokinetic/pharmacodynamic (PK/PD) properties of antibiotics are not well-defined, we have evaluated the PK/PD indices for different regimens of ceftazidime (CAZ; with/without colistin) against Pseudomonas aeruginosa biofilm. Methods: We have used the Center for Disease Control and Prevention Biofilm Reactor with two susceptible (PAO1 and HUB-PAS) and one resistant (HUB-XDR) strains of P. aeruginosa. The regimens were CAZ monotherapies (mimicking a human dose of 2 g/8 h, CAZ-IB; 6 g/daily as continuous infusion at 50 mg/L, CAZ-CI50; and 9 g/daily at 70 mg/L, CAZ-CI70) and CAZ-colistin combinations. Efficacy was correlated with the CAZ PK/PD parameters. Results: CAZ-CI70 was the most effective monotherapy against CAZ-susceptible strains (Δlog CFU/mL 54-0 h = −4.15 ± 0.59 and −3.05 ± 0.5 for HUB-PAS and PAO1, respectively; p ≤ 0.007 vs. other monotherapies), and adding colistin improved the efficacy over CAZ monotherapy. CAZ monotherapies were ineffective against the HUB-XDR strain, and CAZ-CI50 plus colistin achieved higher efficacy than CAZ-IB with colistin. The PK/PD index that correlated best with anti-biofilm efficacy was fAUC0-24h/MIC (r2 = 0.78). Conclusions: CAZ exhibited dose-dependent anti-biofilm killing against P. aeruginosa, which was better explained by the fAUC0-24h/MIC index. CAZ-CI provided benefits compared to CAZ-IB, particularly when using higher doses and together with colistin. CAZ monotherapies were ineffective against the CAZ-resistant strain, independently of the optimized strategy and only CAZ-CI plus colistin appeared useful for clinical practice.